Sustainable bamboo: Technological innovations and patent insights for a greener future - Himalay R. Patel; Rahil Mathakia; Urvashi C. Mangroliya; Viralkumar B. Mandaliya (Advances in Bamboo Science)
Bamboo has emerged as a significant resource across various industries due to its rapid growth rate, strength and sustainability. Despite the many challenges for bamboo and its products, innovative technologies are trying to find a solution and to prepare a greener future. This paper provides a comprehensive patent-based review in four major sectors. A patent landscape analysis on bamboo was conducted using Patentscope (World Intellectual Property Organization database), Scopus Patents, Google Patents, and Lens (a public patent knowledge database). 818 patent records were retrieved from 1898 to 2024 and are discussed sector-wise. Notable patents that exemplify the latest technological strides are highlighted in each area. In the food sector, innovations such as vacuum packaging, natural preservatives and advanced processing methods have improved the shelf life and nutritional integrity of bamboo shoots. In the commercial sector, advances in bamboo fibre extraction and processing have led to higher quality and more sustainable textile products, while innovations in pulping and bleaching processes have reduced the environmental impact of bamboo paper production. In the construction sector, technologies such as laminated bamboo and bamboo composite materials have significantly improved the structural integrity of bamboo, allowing it to be used in load-bearing applications. In the environmental sector, large-scale planting techniques and optimized bamboo plantations have enhanced bamboo’s role in erosion control, land rehabilitation and carbon sequestration. Finally, we demonstrate how bamboo is aligned in achieving Sustainable Development Goals 1–17.